Vaccine-Mediated Mechanisms Controlling Replication of Francisella tularensis in Human Peripheral Blood Mononuclear Cells Using a Co-culture System - Eneslätt, Kjell; Golovliov, Igor; Rydén, Patrik; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2018)
Cell-mediated immunity is normally required for efficient protection against intracellular infections, however, identification of correlates is challenging and they are generally lacking. Francisella tularensis is a highly virulent, facultative intracellular bacterium and cell-mediated immunity is critically required for protection against the pathogen, but how this is effectuated in humans is poorly understood. To understand the protective mechanisms, we established an in vitro co-culture assay to identify how control of infection of F. tularensis is accomplished by human cells and hypothesized that the model will mimic in vivo immune mechanisms. Non-adherent peripheral blood mononuclear cells (PBMC) were expanded with antigen and added to cultures with adherent PBMC infected with the human vaccine strain, LVS, or the highly virulent SCHU S4 strain. Intracellular numbers of F. tularensis was followed for 72 h and secreted and intracellular cytokines were analyzed. Addition of PBMC expanded from naïve individuals, i.e., those with no record of immunization to F. tularensis, generally resulted in little or no control of intracellular bacterial growth, whereas addition of PBMC from a majority of F. tularensis-immune individuals executed static and sometimes cidal effects on intracellular bacteria. Regardless of infecting strain, statistical differences between the two groups were significant, P < 0.05. Secretion of 11 cytokines was analyzed after 72 h of infection and significant differences with regard to secretion of IFN-γ, TNF, and MIP-1β was observed between immune and naïve individuals for LVS-infected cultures. Also, in LVS-infected cultures, CD4 T cells from vaccinees, but not CD8 T cells, showed significantly higher expression of IFN-γ, MIP-1β, TNF, and CD107a than cells from naïve individuals. The co-culture system appears to identify correlates of immunity that are relevant for the understanding of mechanisms of the protective host immunity to F. tularensis.